Epidemiology of traumatic spinal injuries in Brazil: systematic review - Botelho, Ricardo Vieira; Gianini Albuquerque, Luciana Dini; Junior, Rafael Bastianello; Arantes Júnior, Aluízio Augusto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2014)
Prevention remains the most effective way to reduce the burden of spinal injuries (SI). Estimating the incidence and causes of SI is essential for the development of prevention programs. To reveal the current state of Brazilian ST epidemiology. To evaluate the current state of Brazilian SI epidemiology, we performed an electronic search using the Lilacs database (Latin American and Caribbean Health Sciences Literature). Fifteen papers and one unsubmitted ongoing study (BH project) reported the epidemiologic status of ST in Brazil. The mean age of SI patients was 34,75 years, and 84% of patients were male. The most commonly affected segment was the cervical spine (36.65%). The incidence ranged from 16 to 26 patients per million per year (average 21 per million per year). The average rate of complete spinal cord injury among five papers was 34%. The average mortality in four papers was 11.58%. Analyzing published national epidemiological data enables the estimation of the current state of Brazilian SI epidemiology.
Keywords: Epidemiology; spinal cord injuries; spinal fractures